Changes in Hematological Indices in Different Stages of Chronic Renal Failure - Khanam, Shaheda; Begum, Noorzahan; Begum, Shelina; Hoque, AMM Ehteshamul (Journal of Bangladesh Society of Physiologist, 2008)
The study was carried out to observe some aspects of hematological changes like Hb concentration, PCV and TC of RBC in different stages of Chronic Renal Failure(CRF) patients suffering from anemia. For this purpose, 65 male CRF patients with anemia and 25 apparently health male (control) subjects of age ranged from 30-50 years were selected randomly from BSMMU out patient department. Hematological parameters and renal creatinine clearance were estimated by usual laboratory technique. Data were analyzed statistically by ANOVA and Pearson's correlation coefficient test. Among the CRF patients 15 were mild, 25 were moderate and 25 were severe CRF patients with anemia. In this study, the mean Hb concentration, PCV and total count of red blood cells were significantly lower in three stages of CRF patients with anemia compared to those of healthy subjects. Again, all of these hematological values were significantly (P< 0.001) lower in moderate and severe CRF patients compared to mild cases and also in severe cases than those of moderate CRF cases with anemia. All the Hematological parameters showed positive correlation with creatinine clearance in all three stages of CRF and it was statistically significant in moderate and severe group. From the present study it may be concluded that CRF patients with anemia had lower hematological indices and the degree of changes depend on severity of renal failure. Key Words: Hemoglobin; Packed Cell Volume; Renal Failure DOI:10.3329/jbsp.v2i0.983 J Bangladesh Soc Physiol. 2007 Dec;(2): 38-41.